NILAI DAN KEKUATAN PEMBUKTIAN KETERANGAN SAKSI TESTIMONIUM DE AUDITU - Tarigan, Daniel Milano; Rustamaji, Muhammad (Verstek, 2023)
There has been a lot of research on obscenity, but the discussion on the use of testimonium de auditu in obscenity cases is of interest to the author. This thesis aims to examine the value and strength of the evidence of the testimonium de auditu and the testimony suitability of witnesses from the testimony of de auditu in cases of sexual abuse of children under the provisions of criminal procedural law. The type of this research is normative legal research which is prescriptive and applied. This legal research uses a case approach. The legal materials used on this research consist of primary and secondary legal materials. The collection of legal material used in this research use library research. The legal material analysis technique used in this law research is the syllogism method with deductive thinking patterns. Based on the results of the research and discussion, it can be concluded that the value and strength of evidence in criminal procedural law are all of free value to the judge, as well as the testimony of the testimonium de auditu. Keywords: Testimonium De Auditu; Value and strength of evidence; Witness testimony